The Effect of Economic Growth, Fossil Energy Consumption, and Urbanization on The Environmental Quality Index in Indonesia For the Period 2007-2024 - Royhan Agung Kurnia; Ahmad Hazas Syarif; Alief Rakhman Setyanto (Jurnal Ekonomika dan Manajemen, 2026)
The trade-off between achieving economic welfare and maintaining ecological stability remains a critical challenge for developing nations like Indonesia. This study examines the dynamic effects of economic growth, fossil fuel consumption, and urbanization on the Environmental Quality Index (EQI) in Indonesia during the period 2007-2024. Using the Vector Error Correction Model (VECM), the analysis reveals a significant long-term cointegration relationship among the variables. Empirical results show that economic growth has a significant negative impact on environmental quality, confirming the initial stage of the Environmental Kuznets Curve (EKC) hypothesis, in which economic activity is still highly dependent on sectors that degrade the environment. Conversely, urbanization exhibits a positive impact on environmental quality, indicating that urban areas possess more effective environmental governance and resource efficiency compared to rural regions. Although the long-term coefficient of fossil energy consumption is relatively small, Variance Decomposition analysis identifies energy consumption shocks as a persistent determinant of fluctuations in environmental quality. Consequently, this study recommends accelerating the energy transition and strengthening environmental regulations specifically within economic growth centers.